Examining the Testing Effect in University Teaching: Retrievability and Question Format Matter - Greving, Sven; Richter, Tobias (Frontiers in Psychology, 2018)
Review of learned material is crucial for the learning process. One approach that promises to increase the effectiveness of reviewing during learning is to answer questions about the learning content rather than restudying the material (testing effect). This effect is well established in lab experiments. However, existing research in educational contexts has often combined testing with additional didactical measures that hampers the interpretation of testing effects. We aimed to examine the testing effect in its pure form by implementing a minimal intervention design in a university lecture (N = 92). The last 10 min of each lecture session were used for reviewing the lecture content by either answering short-answer questions, multiple-choice questions, or reading summarizing statements about core lecture content. Three unannounced criterial tests measured the retention of learning content at different times (1, 12, and 23 weeks after the last lecture). A positive testing effect emerged for short-answer questions that targeted information that participants could retrieve from memory. This effect was independent of the time of test. The results indicated no testing effect for multiple-choice testing. These results suggest that short-answer testing but not multiple-choice testing may benefit learning in higher education contexts.